(3GdJWhQ GdQGSeGdj (B/s - (3GfOQjja, s ((3ehSch (B:s (3OGQ GdJbOe ,s, 1977)
(3Mhd efGgL HMK WQjb GdJWhQ GddGQGSeGdj(B,(3GdHfjI GdGLJeGYjIGdGbJUGOjIaj HdOGf GdYGde GdKGdK(B,(3GdXQha GdJGQjNjI ddJWhQ GddGQGSeGdj(B,(3GJLGgGJ GdJWhQ GddGQGSeGdjh eQGMdg(B,(3GdgjGcdGdeTGYjI h GdOhdI GdKhQjI GdOjebQGWjI (B,(3JbOe Gdbhi GdefJLI h YdGbGJ GdGfJGL aj Xd GdJWhQ GddGQGSeGdj(B,(3SeGJ GdhYj GdaQOj h GdGLJeGYj aj Xd GdJWhQ GddGQGSeGdj s
Keywords: (3GdETJQGcjIs; (3GdHdOGf GdfGejIs; (3GdQCSeGdjIs